Can Artificial Intelligence and Modern Technologies Address the Common Issues of Consumer Online Dispute Resolution in the EU? - Riepin, Pavlo (Teisė, 2024)
The article examines the current status of Online Dispute Resolution (ODR) in the European Union, explicitly evaluating its advantages and disadvantages. In addition to examining the evolution of the ODR mechanisms, the author sheds light on the challenges encountered in their implementation, such as concerns about trust, transparency, and accessibility. Moreover, this analysis investigated the potential implications of artificial intelligence and contemporary technologies on the transformation of the EU’s consumer ODR framework. The ADR/ODR system of the EU has been subject to criticism for several weaknesses, including inconsistent implementation, insufficient supervision, and the lack of mandatory participation for traders. The lack of a specialised supervisory mechanism has also led to shortcomings in the oversight process. The Directive does not impose a requirement for traders to participate in ADR procedures; nevertheless, there exists significant heterogeneity in the regulations that govern these procedures. The lack of binding enforcement for final decisions arises from the requirement of Member States to agree upon and acknowledge the mechanisms for recognition and implementation. The EU ODR Platform operates as a mechanism for referring cases to ADR bodies. Nevertheless, the entity in question does not actively participate in the resolution of disputes based on their substantive merits, and its jurisdiction is primarily limited to smaller entities. Artificial intelligence (AI) has the potential to enhance transparency, objectivity, and legitimacy within online dispute resolution systems, thereby potentially giving rise to a two-tier system. The author suggests that in order to bring about significant legislative changes, it is necessary to incorporate certain provisions. These provisions should mandate the enforcement of decisions made in alternative dispute resolution (ADR) processes for consumers and also facilitate the seamless integration of artificial intelligence (AI) into this system. Otherwise, it is unlikely that AI will substantially impact the efficiency and effectiveness of the EU ADR/ODR system, as its primary challenges are rooted in areas beyond the scope of AI, such as the enforcement of decisions.